2012
DOI: 10.1038/tp.2012.122
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the adolescent brain to cannabinoids: long-term hippocampal effects and relevance to schizophrenia

Abstract: Clinical studies report associations between cannabis use during adolescence and later onset of schizophrenia. We examined the causal relationship between developmental cannabinoid administration and long-term behavioral and molecular alterations in mice. Mice were administered either WIN 55,212-2 (WIN), a cannabinoid receptor 1 (CB1) agonist or vehicle (Veh) during adolescence (postnatal day 30–35) or early adulthood (postnatal day 63–70). Behavioral testing was conducted after postnatal day 120 followed by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 93 publications
3
39
0
1
Order By: Relevance
“…(55)). Echoing these limited findings in humans, preclinical studies showed that mice treated with cannabinoids during adolescence have sustained, markedly increased FAAH protein concentrations in the hippocampus in adulthood (33); as well, THC-tolerant rats have significantly decreased AEA concentrations in the striatum and midbrain although opposite findings were observed in the limbic forebrain and no change was observed in other brain regions including hippocampus, suggesting possible regionally specific FAAH modulation following chronic CB1 stimulation (31, 32). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(55)). Echoing these limited findings in humans, preclinical studies showed that mice treated with cannabinoids during adolescence have sustained, markedly increased FAAH protein concentrations in the hippocampus in adulthood (33); as well, THC-tolerant rats have significantly decreased AEA concentrations in the striatum and midbrain although opposite findings were observed in the limbic forebrain and no change was observed in other brain regions including hippocampus, suggesting possible regionally specific FAAH modulation following chronic CB1 stimulation (31, 32). …”
Section: Discussionmentioning
confidence: 99%
“…Although it may be expected that development of tolerance to cannabinoids is also associated with changes in AEA concentrations and FAAH activities (2628), few studies addressed this question in THC-dependent animals or humans. In this regard, studies by Leweke and colleagues of human cannabis users reported lower levels of AEA in cerebral spinal fluid (CSF) of frequent versus occasional users and healthy controls (a trend, (29, 30)), which is supported by some preclinical data (31, 32) and suggests that heavy chronic cannabis exposure might be associated with elevated brain FAAH activities (33, 34) and that targeting FAAH might be useful for cannabis withdrawal. Indeed, the FAAH inhibitor URB597 reduced rimonabant-precipitated withdrawal in THC-dependent mice (17).…”
Section: Introductionmentioning
confidence: 91%
“…Several recent genome-wide association studies confirmed the involvement putative SNPs in GRM5 (Matosin et al, 2015b). In animal models, administration of cannabinoids during adolescence were shown to a reduction in hippocampal mGluR5, which was associated with learning deficits (Gleason et al, 2012). In contrast, postmortem studies have found only minimal changes in mGluR5 mRNA and mGluR5 protein in schizophrenia (Corti et al, 2011;Gupta et al, 2005;Volk et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Cognitive deficits in associative fear memory have been reported in mice displaying schizophrenic-like phenotypes (Arguello and Gogos, 2006;Gleason et al, 2012). Fear conditioning was assessed in computer-controlled operant chambers (Imetronic), as previously described (Blundell et al, 2010;Cai et al, 2006;Powell et al, 2004).…”
Section: Contextual and Cued Fear Conditioningmentioning
confidence: 99%